2019
DOI: 10.1090/tran/7840
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity of algebras associated to non-Hausdorff groupoids

Abstract: We prove a uniqueness theorem and give a characterization of simplicity for Steinberg algebras associated to non-Hausdorff ample groupoids. We also prove a uniqueness theorem and give a characterization of simplicity for the C * -algebra associated to non-Hausdorffétale groupoids. Then we show how our results apply in the setting of tight representations of inverse semigroups, groups acting on graphs, and self-similar actions. In particular, we show that the C * -algebra and the complex Steinberg algebra of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 28 publications
(64 reference statements)
1
63
0
Order By: Relevance
“…for all α ∈ G, αs(α) = r(α)α = α holds, (3) for all (α, β) ∈ G (2) , s(αβ) = s(β) and r(αβ) = r(α) hold,…”
Section: éTale Groupoids and Groupoid C*-algebrasmentioning
confidence: 99%
See 2 more Smart Citations
“…for all α ∈ G, αs(α) = r(α)α = α holds, (3) for all (α, β) ∈ G (2) , s(αβ) = s(β) and r(αβ) = r(α) hold,…”
Section: éTale Groupoids and Groupoid C*-algebrasmentioning
confidence: 99%
“…every γ ∈ G, there exists γ ∈ G which satisfies (γ , γ), (γ, γ ) ∈ G (2) and s(γ) = γ γ and r(γ) = γγ . Since the element γ in (5) is uniquely determined by γ, γ is called the inverse of γ and denoted by γ −1 .…”
Section: éTale Groupoids and Groupoid C*-algebrasmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases with the assumption that G is amenable, it has been shown that O Gmax and O Gmin are isomorphic by proving the simplicity of the reduced groupoid C * -algebra. See [3,11]. It is one of a problems on the C * -algebraic aspect that several Cuntz-Pimsner algebras from a self-similar group action might not be isomorphic especially in non-amenable case.…”
Section: Introductionmentioning
confidence: 99%
“…If G is an amenable group, O Gmin and O Gmax are isomorphic in some cases. See[3,11] for example. To understand O Gmin we consider another algebra from self-similar actions.…”
mentioning
confidence: 99%